Accessibility for physically challenged persons in heritage buildings / Phan Meng Hooi - Phan, Meng Hooi (2016)
Inscription of UNESCO World Heritage Sites to George Town, Penang and Historical Straits of Malacca in 2008 has elevated heritage tourism of Malaysia to be one of the main proponents continually to boost our economy. Researches have learnt preserving local resources especially heritage capital to heritage tourism and improving social interest like accessibility needs for persons with disabilities could constitute to quality tourism. At the same time, it is parallel with regional proclamation to achieve ‘inclusive, barrier free and right based society’ approach in Asia Pacific region. It leads the research to explore whether thinking about accessibility needs for persons with physical disabilities within heritage properties happen in Malaysia. The pilot case studies in Malacca and Penang ascertained inception of the approach coexists in Malaysia yet it is still a new phenomenon and attempt in national planning since enforcement of the Persons with Disabilities Act 2008 and amendment to UBBL 34A to make public building accessible for all. Besides, the tested case study protocol derived an inventory to assist the existing checklist in access auditing on heritage buildings. The direct observation was then conducted by the checklist and inventory on replicated case study in selection from George Town based on variation of the researched phenomenon and heritage attributes. Due to study encountered each conservation work has unique heritage significance in case study especially Leong San Tong Khoo Kongsi, St. George Church and Suffolk House in George Town. The access auditing on multiple-case study indicated access problems on restored key elements of heritage buildings as perceived under current practicing local guidelines and code of practices. Eventually conflicts were revealed in convergence of barrier free environment and conservation approach. Conversely research justified appropriate access could be addressed under reasonable accommodation to enclave gaps between both principles. The design adjustment could be guided within degree of intervention and intensity of use to meet the minimum level of easy access without adversely effecting heritage significance and authenticity of heritage property. The minimum level of accessibility are attainable by the identified fundamental nine core elements along sequence of journey through the heritage site from pre-information until leaving the site at the end of visiting. Certainly there is never a fixed standard in proposing accessible heritage due to heritage significance and conservation planning varies in cases basis. In turn, what are the scale to measure equilibrium between both contradict approaches could be researched in future.